Effect of integrated copper pad on the performance of boiling-driven wickless thermal ground plane - Moon, Joo Hyun; Wang, Xiaomeng; Fadda, Dani; Shin, Dong Hwan; Lee, Jungho; You, Seung M. (Applied Thermal Engineering, 2021)
A solid copper pad is integrated into the heating side of a wickless copper thermal ground plane (TGP) with deionized water as the working fluid. Experimental TGP performance tests, along with pool boiling experiments and conduction thermal numerical simulations, are used to quantify the effect of the copper pad thickness on the overall thermal performance of the TGP. Even though adding the copper pad weakens the effective thermal conductivity of the TGP slightly, it improves the dryout within the TGP and allows operation at up to 1.6 times higher heat flux value. Boiling inside the TGP yields a reduced boiling heat transfer coefficient in the narrow gap, coupled with a higher dryout point due to the bubble-induced flow inside the TGP. The effective thermal conductivity remains 1.5 to 1.8 times higher than that of plain copper, and the weight of the TGP is approximately 60% of the weight of a solid copper block of the same size. The TGP is orientation-independent regardless of the pad thickness and water amounts.
Keywords: Boiling-driven; Deionised waters; Effective thermal conductivity; Ground planes; Heat spreading; Orientation-independent; Performance; Thermal; Thermal ground plane; Wickless; Boiling-Driven; Heat Spreading; Orientation-Independent; Thermal Ground Plane; Wickless